Determain Kind and Concentration of Allium sativum L.Plant Ingredients and its Effect on Isolated Bacteria Causing Urinary Tract Infections - Ayyub J. Abdl-Rahmaan Al-Baytay (Journal of Global Pharma Technology, 2016)
Atotal of  (190)  samples urinary were collected patients with Urinary Tract Infections(UTIs) from the period 2017/11/18 to 2018/2/17 ,for determain kind and concentration of Allium sativum L.ingredients and its effect on growth of the Gram-negative bacteria isolated from urinary tract infections in Al-Alam city/Tikrit Governoratr/Iraq,The study was carried out in the laboratories of Al-Alam Hospital and the laboratories of the College of Education for Women , Department of life Science,chemical analysis by HPLC apparatua showed the plant contain severel active ingrdients: S-ally cysteine,Y-glutomycysteine, Vinyl-{4H}1,2dithlin(agoene),di-allyldisulfide and Diallytrisulfide with concentrate,5.72% 9.75%, 53.09%,9.72%,12..85% and 10.60% respectively,also appeared many bacteria genus on In the samples taken from patients patients: E.coli, Klebsiella, Pseudomonus,Proteus,Serratia and Chromobacterium with isolates concentration reached for each genus reached, 44.2%, 23.5%, 17.6%, 5.5%, 5.8% and 2.9% respectively,and the current study for aquoues and alcoholic for  extracts appeared a clear contrast on inhibition of studied bacteria kinds, as it was alcoholic extract of Allium sativum more inhibiton than aquoues extract on the concentration 100% throught observation inhibition diameter on the concentration 25,50 and 100%.Keywords: Allium sativum+plant extract+bacteria.